Fecal calprotectin levels in pediatric cow's milk protein allergy - Lendvai-Emmert, Dominika; Emmert, Vanessza; Makai, Alexandra; Fusz, Katalin; Prémusz, Viktória; Eklics, Kata; Sarlós, Patrícia; Tóth, Péter; Amrein, Krisztina; Tóth, Gergely (Frontiers in Pediatrics, 2022)
Introduction: The most prevalent food allergy in younger children is cow’s milk protein allergy (CMPA), a hypersensitivity reaction to cow’s milk protein and its most common clinical manifestation is allergic colitis. The goal of our recent study was to assess somatic symptoms of CMPA and to prospectively observe the effects of a dairy elimination diet using objective parameters and questionnaires. Methods: Children aged 1-18 years with clinical signs suggesting CMPA were examined at the County Hospital, Szekszárd, Hungary. Stool samples were collected at the time of the diagnosis and after 3 months of elimination diet followed by analysis with a fecal calprotectin (FC) rapid test (Quantum Blue fCAL, Bühlmann Laboratories, Switzerland). Questionnaires were completed at baseline and at the first and second follow-up. Based on the results of the questionnaires, patients were divided into two subgroups according to dietary rules. Results: A total of 47 patients were included in the study [42.55% female, mean age: 7.36 (SD 4.22) years]. There was no significant difference in FC levels between baseline and after 3-month elimination diet [73.98 (71.12) μg/g and 68.11 (74.4) μg/g, respectively, p=0.331]. Among those patients who followed the strict diet correctly, a significant decrease in FC levels was observed after three months [84.06 (79.48) μg/g and 41.11 (34.24) μg/g respectively, p <0.001]. Conclusion: The findings of our study suggest that FC can be an objective parameter in confirming the diagnosis of CMPA. Significant improvement in clinical symptoms and in FC levels can only be expected after a strictly followed elimination diet.